Circulating branched-chain amino acids and the risk of major adverse cardiovascular events in the UK biobank - Sun, Wanwan; Lin, Ruilang; Li, Yiming; Yao, Ye; Lu, Bin; Yu, Yongfu (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the relationship between circulating branched-chain amino acids (BCAAs) and the risk of major adverse cardiovascular events (MACE) in a national population-based cohort study.MethodsUK Biobank, a prospective study involving 22 recruitment centers across the United Kingdom. For this analysis, we included 266,840 participants from the UK Biobank who had available BCAA data and no history of MACE at baseline. Cox regression analysis was conducted to evaluate these associations, adjusting for potential confounders.ResultsDuring a 13.80 ± 0.83-year follow-up, 52,598 participants experienced MACE, with the incidence of MACE increasing progressively across quintiles of circulating BCAAs, isoleucine, leucine, and valine. Overall, the fifth quintile exhibited a 7-12% higher MACE risk compared to the second quintile. In males, BCAAs were not associated with MACE risk. However, increased risks were observed for isoleucine (8-12% in higher quintiles), leucine (9% in the first quintile and 6% in the fifth quintile), and valine (8% in the first quintile). In females, higher quintiles of BCAAs, isoleucine, leucine, and valine were associated with increased MACE risk, ranging from 9% to 12%. Among participants under 65y, higher quintiles of BCAAs, isoleucine, and leucine were associated with increased MACE risk, while valine showed no significant association. No association was found in participants aged 65 and older. These analyses were adjusted for multiple potential confounders.ConclusionGenerally, higher levels of BCAAs, isoleucine, leucine, and valine were associated with an increased risk of MACE, except in participants older than 65. Additionally, in males, the lowest quintiles of leucine and valine were also associated with an increased risk of MACE.